Salmonella in pork retail outlets and dissemination of its pulsotypes through pig production chain in Chiang Mai and surrounding areas, Thailand - Prapas Patchanee (2018)
© 2016 Elsevier B.V. Salmonella spp. is acknowledged as a significant zoonotic foodborne pathogen throughout the world. Contaminated pork consumption is considered as a main cause of human salmonellosis. In the later stage of the pig production chain, poor hygiene and unsuitable storage conditions in retail outlets are considered to be key factors linked to the risk of Salmonella infection. The purpose of current study, which was conducted throughout April 2014 to September 2014, was to determine the prevalence and characteristics of Salmonella spp. in pork sold at the retail stage in wet markets and supermarkets in the Chiang Mai urban area of Thailand. Additionally, clonal relations between Salmonella strains described in this study and those identified in earlier study from the same geographical area were considered. It is provided as a means of contributing to current knowledge regarding Salmonella epidemiology with an ultimate aim of improved food security and consumer protection in this region. From a total of 82 pork samples analyzed in this study, 41% were positive for Salmonella, with prevalence of 73.2% from wet markets (n = 30/41) and 9.8% from supermarkets (n = 4/41). Twelve Salmonella serovars were identified, S. Rissen being the most commonly encountered. Antibiotic resistance of the isolates was highest for ampicillin and tetracycline (53%), followed by streptomycin (44%). Pulsed-field gel electrophoresis (PFGE) and subsequent geographical distribution analysis indicated that the clonal Salmonella strains originated from multiple sources had been spread over a wide area. The existence of a common pig supply chain “farm-slaughterhouse-retail” transmission route is inferred. Continuous monitoring of Salmonella along the entire production chain is needed to reduce contamination loads and to ensure the safety of pork products for end consumers.